Cumulative exposure to maternal psychological distress in the prenatal and postnatal periods and atopic dermatitis in children: findings from the TMM BirThree Cohort Study - Chikana Kawaguchi; Keiko Murakami; Mami Ishikuro; Fumihiko Ueno; Aoi Noda; Tomomi Onuma; Fumiko Matsuzaki; Hirohito Metoki; Shinichi Kuriyama; Taku Obara (BMC, 2022)
Abstract Background Maternal mental health problems in each of the prenatal period and postnatal period have been demonstrated as possible risk factors for atopic dermatitis (AD) in children. However, the cumulative impacts of maternal psychological distress in the prenatal and postnatal periods on AD in children remain unclear. This study examined the association between cumulative exposure to maternal psychological distress in the prenatal and postnatal periods and the development of AD in children. Methods Data were derived from the Tohoku Medical Megabank Project Birth and Three-Generation Cohort Study in Japan. In total, 8377 mother-child pairs in which the child had no AD at the age of 1 year were analyzed. Maternal psychological distress in early pregnancy and 1 year after delivery was defined as a K6 score ≥ 5, and the participants were categorized into four groups: no psychological distress in both the prenatal and postnatal periods; only the prenatal period; only the postnatal period; and both periods. The development of AD was defined as the presence of AD in a 2-year-old child without AD reported at the age of 1 year using the International Study of Asthma and Allergies in Childhood questionnaire. Generalized linear model analyses were conducted to examine the association between maternal psychological distress and the development of AD in children adjusted for age at delivery, educational attainment, smoking status in pregnancy, maternal history of AD, paternal history of AD, parity, maternal body mass index, and child sex. Results Between the ages of 1 and 2 years, 14.0% of children developed AD. Maternal psychological distress in both prenatal and postnatal periods was associated with an increased risk of AD in children compared to no psychological distress in both periods (relative risk (RR), 95% confidence interval (CI): 1.34, 1.20-1.47). Maternal psychological distress in only the postnatal period was associated with an increased risk of AD in children (RR, 95% CI: 1.23, 1.07-1.39), but not in only the prenatal period (RR, 95% CI: 1.14, 0.98-1.30). Conclusions Cumulative exposure to maternal psychological distress in the prenatal and postnatal periods was associated with the development of AD in children.